Pengaruh Pembayaran SPaylater dan Potongan Harga terhadap Keputusan Pembelian Produk Fashion pada pengguna Shopee di Surabaya - Nasikhudinn, Muhammad; Maduwinarti, Ayun; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
Needs are everything that is needed by humans to maintain and develop their survival, the form of needs can be in the form of goods and services. In the current 5.0 era, people have started using marketplace applications to meet their needs, which provide various needs such as clothing, electronic devices, food, etc. One of them is the Shopee marketplace, Shopee does a lot of promotions to attract potential customers. Promotions provided by the Shopee marketplace are providing SPaylater payment facilities and price discounts to attract consumers to use and purchase goods or services at Shopee. Therefore, this research was carried out with the aim of analyzing whether Spaylater Payments and Price Discounts affect Purchase Decisions for fashion products for Shopee users in Surabaya, this research is a type of Quantitative research, the object of this research is consumers who have purchased fashion products from Shopee users in Surabaya. with a total sample of 100 using a purposive non-probability sampling technique. The data collection technique in this study used an electronic questionnaire included in the Google form, and will then be analyzed with the help of the SPSS application. The results that have been obtained from a series of tests that have been carried out, namely the SPaylater Payment Variable and Price Discounts, have an influence on the Purchase Decision of fashion products for Shopee users in Surabaya